Environmental enrichment does not compromise the immune response in mice chronically infected with Mycobacterium avium - Olsson, I. A. S. (2010)
Research on infectious diseases using animal models has been a successful example of translational research. However, because chronic infections are still one of the main causes of death and disability in the world, it is expected that a great number of mice will continue to be used to address this subject. Although increasing awareness regarding animal welfare has led to novel recommendations for animal housing enrichment, studies evaluating the impact of these modifications on the immune response to infection are lacking. The present study shows that validated and recommended simple environmental enrichment does not interfere with the immune response to chronic infection with Mycobacterium avium for up to 20 weeks, as assessed by the bacterial load in the spleen and lung, by the number and activation status of the main cell populations of the immune system and the serum concentration of interferon-gamma. Therefore, enrichment can be encouraged without concern regarding comparability of results among laboratories studying this type of chronic infections.